Penerapan Media Pembelajaran Interaktif Sistem Tata Surya Di Kelas Vi Sdn Leuwiranji 03 - Nadia Farah Annisa; Risa Amalia Febrianti; Reza Primatama (Program Studi PGSD Kampus UPI di Serang, 2021)
This research was conducted to describe how the application of interactive learning media in learning the solar system teaching materials for class vi thematic books at sdn leuwiranji 03 was applied by researchers. This study also describes how the responses or responses from students in carrying out the learning process using interactive learning media. This research is descriptive qualitative research. The subjects in this study were students who carried out learning using learning media. The object of research is focused on the application of interactive learning media for the solar system and the responses of students in the application, in terms of media design, and students' understanding after carrying out the learning process. Collecting data using observation techniques, questionnaires, and document analysis. In analyzing the data using qualitative descriptive analysis techniques. The results of the study show how the application of interactive learning media